Стан забезпечення охорони праці працівників поліції у сучасних умовах - Клочко, І. О.; Klochko, I. O. (Юридична наука. - 2019. - № 12 (102), т. 2. - С. 324-331, 2019)
Аргументовано, що на сьогоднішній день стан забезпечення охорони праці працівників поліції слід оцінити як незадовільний, про що свідчать статистичні дані та правозастосовна практика. Виокремлено напрямки, в яких необхідно покращувати забезпечення охорони праці працівників поліції.

The article emphasizes that it is possible to provide an objective assessment of the state of labor protection of police officers through the analysis of key elements of this system. Based on the analysis of scientific views of scientists and current legislation, it was argued that today the state of labor protection of police officers should be assessed as unsatisfactory, as evidenced by statistics and law enforcement practice. The areas in which it is necessary to improve the protection of labor protection of police officers are identified. It was concluded that today the state of ensuring labor protection of police officers should be assessed as unsatisfactory. This fact is evidenced by statistical data and law enforcement practice. Our analysis allows us to state that the problems of labor protection of police officers exist in the following areas: – legal, which is caused by the presence of a number of gaps and shortcomings in the current general and special legislation. The situation is worsened by the fact that to date there is no single legislative act in the departmental legal base that would regulate the very issue of occupational health and safety of police officers; - organizational, because quite often the management and administrative activity of the heads of police bodies and units is unsystematic and does not meet the modern challenges that police officers have to face in the course of their daily work activities. In addition, the system of supervision and control over compliance with the legislation on the labor protection of police officers is not effective; – economic, because the labor protection system of police officers is currently characterized by insufficient financial and economic support; – educational methodical, since scientific and pedagogical work in the direction of improving the labor protection of police officers is not actually being conducted today; – sanitary and hygienic. In this context, we note that there are currently no clear legal and organizational conditions regarding what the sanitary and hygienic provision of labor protection of police officers in Ukraine should be.

Аргументировано, что на сегодняшний день состояние обеспечения охраны труда работников полиции следует оценить как неудовлетворительное, о чем свидетельствуют статистические данные и правоприменительная практика. Выделены направления, в которых необходимо улучшать обеспечение охраны труда сотрудников полиции.
The state of labor protection of police officers in modern conditions
Клочко, І. О. Стан забезпечення охорони праці працівників поліції у сучасних умовах / Клочко І. О. // Юридична наука. - 2019. - № 12 (102), т. 2. - С. 324-331.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; працівники поліції; police officers; работники полиции; охорона праці; labor protection; охрана труда; правове регулювання; legal regulation; правовое регулирование